HEALTH CARE PROVIDERS’ VIEWS CONCERNING KNOWLEDGE AND PRACTICES OF TRADITIONAL BIRTH ATTENDANTS IN TAJIKISTAN: A QUALITATIVE STUDY - Dilofarid Miskinzod (Global Journal of Public Health Medicine, 2021)
Introduction: This study seeks to explore health care providers’ perspectives of the traditional birth attendants’ knowledge and practices. Methods: This qualitative study was conducted in 2018 with 16 health care professionals working at various levels of maternal health care system in two purposefully selected research settings, Khorog town and Dushanbe, which have different social, economic and ethnic backgrounds. Semi-structured face-to-face interviews were conducted to gather the data. Duration of interviews ranged from 30-60 min. NVivo software for qualitative research was used to analyse the results. Results: This study has shown that health care workers have extremely negative views of the knowledge and practices of traditional birth attendants. They highlight the lack of adequate knowledge of traditional birth attendants on biomedical aspects of birth, poor skills in infections control and lack of use of clean delivery practices. They also claim that the traditional birth attendants’ practices also lead to different complications while they are woefully unprepared to recognize obstetric complications during birth. Conclusion: The study recommends providing a skilled birth attendant in every area. It also recommends avoiding a homogeneous approach to address maternal health issues in diverse countries of the Global South and reviewing maternal health care policies and programs to provide the most marginalized groups of women with skilled birth services to improve their maternal health and further decrease maternal mortality in Tajikistan.